Utilizing Digital Interactive Boards And Student Room Platforms In The Digitalization Of Early Childhood Education: The Opportunities And Challenges - Norhikmah, Norhikmah; Miftah, M. Zaini; Asmawati, Asmawati; Sardimi, Sardimi; Jasiah, Jasiah (UIN Sultan Maulana Hasanudin Banten, 2026)
This study aims to analyze the opportunities and challenges of utilizing Digital Interactive Boards (PID) and the Ruang Murid Platform (Student Room Platform) in the digitalization of Early Childhood Education (ECE). This study employed a qualitative approach using a library research method. Data were obtained from scientific journals, books, and relevant research articles, then analyzed descriptively and analytically. The findings show that the utilization of PID and the Ruang Murid Platform is able to create more interactive and varied learning, support children’s learning engagement, and strengthen communication between teachers and parents. However, the implementation of digitalized learning in ECE still faces challenges, including limited teachers’ digital competence, inadequate facilities and infrastructure, and low parental involvement in the use of digital platforms. In addition, the use of technology in ECE needs to be implemented proportionally so that it does not reduce children’s social interaction, play activities, and concrete learning experiences. Therefore, collaboration among teachers, parents, and educational institutions is needed to optimize sustainable digital-based learning in ECE.